Fake source‐based source location privacy in wireless sensor networks. (1st April 2014) - Jhumka, Arshad; Bradbury, Matthew; Leeke, Matthew; Xiang, Yang; Al‐Dubi, Ahmed; Liu, Lei; Chu, Xiaowen
Summary The development of novel wireless sensor network (WSN) applications, such as asset monitoring, has led to novel reliability requirements. One such property is source location privacy (SLP). The original SLP problem is to protect the location of a source node in a WSN from a single distributed eavesdropper attacker. Several techniques have been proposed to address the SLP problem, and most of them use some form of traffic analysis and engineering to provide enhanced SLP. The use of fake sources is considered to be promising for providing SLP, and several works have investigated the effectiveness of the fake sources approach under various attacker models. However, very little work has been done to understand the theoretical underpinnings of the fake source technique. In this paper, we (i) provide a novel formalisation of the fake sources selection problem; (ii) prove the fake sources selection problem to be NP‐complete; (iii) provide parametric heuristics for three different network configurations; and (iv) show that these heuristics provide (near) optimal levels of SLP under appropriate parameterisation. Our results show that fake sources can provide a high level of SLP. Our work is the first to investigate the theoretical underpinnings of the fake source technique. Copyright © 2014 John Wiley & Sons, Ltd.